Relationships of ferroptosis-related genes with the pathogenesis in polycystic ovary syndrome - Lin, Shuang; Jin, Xin; Gu, He; Bi, Fangfang (Frontiers in Medicine, 2023)
Background: Numerous studies suggest that ferroptosis plays an important role in the development of PCOS, but the mechanism remains unclear. In this study, we explored the mechanism of ferroptosis related genes in the pathogenesis of PCOS using comprehensively bioinformatics method. Methods: Multiple bioinformatic methods were performed, such as differential expression analysis, least absolute shrinkage selection operator (LASSO) regression, support vector machine (SVM-RFE), survival analysis, receiver operator characteristic curve (ROC) analysis, decision curve analysis (DCA), drug sensitivity analysis, nomogram model and ceRNA network construction. Results: GSE5850, GSE34526 and GSE102293 datasets were downloaded from the Gene Expression Omnibus (GEO) database. Five genes, including NOX1, ACVR1B, PHF21A, FTL and GALNT14, were identified and used to construct a PCOS diagnostic model. Drug sensitivity analysis indicated that six drugs or molecular compounds were found to interact with GALNT14 or NOX1. Finally, a ceRNA network including 117 lncRNAs, 67 miRNAs and the 5 ferroptosis related genes was constructed. Conclusions: Our study identified a 5- ferroptosis related genes that might be involved in the pathogenesis of PCOS, which may provide a novel perspective for clinical diagnosis and treatment of PCOS.